SARS-CoV-2 Antibody Isotypes in Systemic Lupus Erythematosus Patients Prior to Vaccination: Associations With Disease Activity, Antinuclear Antibodies, and Immunomodulatory Drugs During the First Year of the Pandemic - Sjöwall, Johanna; Azharuddin, Mohammad; Frodlund, Martina; Zhang, Yuming; Sandner, Laura; Dahle, Charlotte; Hinkula, Jorma; Sjöwall, Christopher (Frontiers in Immunology, 2021)
Objectives: Impact of the SARS-CoV-2-pandemic on individuals with arthritis has been highlighted whereas data on other rheumatic diseases, e.g. systemic lupus erythematosus (SLE), are scarce. Similarly to SLE, severe SARS-CoV-2 infection includes risks for thromboembolism, an unbalanced type I interferon response, and complement activation. Herein, SARS-CoV-2-antibodies in longitudinal samples collected prior to vaccination were analyzed and compared to SLE progression and antinuclear antibody (ANA) levels. Methods: 100 patients (83 women) with established SLE and a regular visit to the rheumatologist (March-2020 to January-2021) were included. All subjects donated blood and had done likewise prior to the pandemic. SARS-CoV-2-antibody isotypes (IgG, IgA, IgM) to the cell-receptor binding S1-spike outer envelope protein were detected by ELISA and neutralization capacity investigated. IgG-ANA were measured by multiplex technology. Results: During the pandemic, 4% had PCR-confirmed infection but 36% showed SARS-CoV-2-antibodies of ≥1 isotype; IgA was the most common (30%), followed by IgM (9%) and IgG (8%). The antibodies had low neutralizing capacity and were detected also in pre-pandemic samples. Plasma albumin (P=0.04) and anti-dsDNA (P=0.003) levels were lower in patients with SARS-CoV-2-antibodies. Blood group, BMI, smoking habits, complement proteins, daily glucocorticoid dose, use of hydroxychloroquine, or self-reported COVID-19-symptoms (except fever, >38.5°C) did not associate with SARS-CoV-2-antibodies. Conclusion: Our data from early 2021 indicate that a large proportion of Swedish SLE patients had serological signs of exposure to SARS-CoV-2, but apparently with a minor impact on the SLE-course. Use of steroids and hydroxychloroquine showed no distinct effects, and self-reported COVID-19-related symptoms correlated poorly with all antibody isotypes.